Plasma-etched Hofmann metal coordination polymer, preparation method thereof and application of plasma-etched Hofmann metal coordination polymer in oxygen evolution reaction
The NiFe-Ni PBA nanosheets were processed through plasma etching technology to promote their reconstruction into NiOOH/FeOOH nanosheets, which solved the problem of insufficient catalytic performance and stability of Hoffman-type coordination polymer materials, and achieved efficient catalytic effect under alkaline conditions.
Patent Information
- Application Number
- CN202411851450.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The existing Hoffman-type coordination polymer materials have poor performance during catalytic oxygen evolution reactions and are insufficient in stability, making it difficult to efficiently and stably catalyze the electrolytic oxygen evolution reaction under alkaline conditions.
The NiFe-Ni PBA nanosheet powder is processed by plasma etching technology to form carbon and nitrogen vacancies and metal defects, and promote its deep reconstruction into NiOOH/FeOOH nanosheets, thereby improving catalytic performance and stability.
The catalytic activity and stability of Hoffmann metal coordination polymer under alkaline conditions have been significantly improved through plasma etching technology, so that it can efficiently and stably catalyze the electrolytic oxygen evolution reaction, with good application prospects.
Smart Images

Figure CN119685867A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalyst materials, and in particular to a plasma-etched Hofmann metal coordination polymer and a preparation method thereof and application thereof in oxygen evolution reaction. Background Art
[0002] The oxygen evolution reaction (OER) is a reaction involving multiple electron transfer processes. Its kinetics are extremely slow, which restricts the development of new energy storage and conversion technologies such as rechargeable metal-air batteries, water electrolysis to produce hydrogen, and electrocatalytic carbon dioxide reduction. Therefore, it is urgent to develop efficient electrocatalysts to accelerate the OER reaction kinetics and thus improve the performance of these new energy devices. At present, commercial OER electrocatalysts are mainly precious metal oxides, and their high prices and scarcity make them difficult to apply on a large scale. Therefore, electrocatalysts that can efficiently and stably catalyze the oxygen evolution reaction in water electrolysis under alkaline conditions are of great practical significance.
[0003] The Chinese patent application document with publication number CN112048072A discloses a method for preparing a Hofmann-type coordination polymer nanomaterial, wherein a plurality of metal M salts are dissolved in deionized water to obtain a mixed solution; K 2 [M′(CN) 4 ] was dissolved in deionized water to obtain K 2 [M′(CN) 4 ] solution; K 2 [M′(CN) 4 ] solution is added to the mixed solution obtained above, stirred, aged at room temperature for 4 to 48 hours, and the formed precipitate is washed, centrifuged, and dried to obtain; the micro-nano material prepared by this patent has the characteristics of multi-dimensionality, multiple growth modes, and uniform size, and the Hofmann-type coordination polymer nanomaterial has potential application prospects in the field of photoelectrocatalysis. However, the catalytic performance of the Hofmann-type coordination polymer material of this patent is poor, so it needs to be further improved. Summary of the invention
[0004] The technical problem to be solved by the present invention is how to improve the catalytic performance and stability of Hofmann-type coordination polymer materials.
[0005] The present invention solves the above technical problems through the following technical means:
[0006] The first aspect of the present invention provides a method for preparing a plasma-etched Hofmann metal coordination polymer, comprising the following steps:
[0007] S1, potassium tetracyanonic acid (K 2 Ni(CN) 4 ) were dissolved in deionized water to prepare solution A, and then ferrous sulfate (FeSO4 ) and nickel nitrate (Ni(NO3)2) are dissolved in deionized water to prepare a solution B, then the solution A and the solution B are mixed, left to stand for a period of time at room temperature (to age the mixed solution), centrifuged, washed, and dried to obtain NiFe-Ni PBA nanosheet powder;
[0008] S2. Evenly spread NiFe-Ni PBA nanosheet powder on a quartz plate, place it in a radio frequency plasma reaction device, and perform plasma etching treatment under an argon atmosphere to obtain.
[0009] Preferably, in S1, the molar ratio of potassium tetracyanonickelate, nickel nitrate and ferrous sulfate is (3-5):(2-4):(0.5-1.5), and more preferably 4:3:1.
[0010] Preferably, in S2, the pressure of the plasma etching treatment is 40-60 Pa, the power is 250-350 W, and the time is 8-15 min; more preferably, it is 50 Pa, 300 W, and 10 min.
[0011] The second aspect of the present invention provides a plasma-etched Hofmann metal coordination polymer obtained by the above preparation method.
[0012] The third aspect of the present invention proposes the use of the above plasma-etched Hofmann metal coordination polymer in the preparation of nickel oxyhydroxide / iron oxyhydroxide heterostructure catalysts.
[0013] The fourth aspect of the present invention proposes a method for preparing a nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst, comprising the following steps: loading the above-mentioned plasma-etched Hofmann metal coordination polymer on a hydrophilic carbon cloth as a working electrode, Hg / HgO as a reference electrode, and a carbon rod as a counter electrode to form a three-electrode system, using potassium hydroxide as an electrolyte, and activating it by a constant voltage method to obtain the catalyst.
[0014] Preferably, in the constant voltage method for activation, the voltage is 1 to 3 V and the activation time is 8 to 15 h; more preferably, it is 1.82 V and 11 h.
[0015] Preferably, the hydrophilic carbon cloth needs to be washed before use. The specific steps are: soak the hydrophilic carbon cloth in concentrated sulfuric acid for 24 hours, then wash it with deionized water and alcohol ultrasonically, and dry it at 60°C for storage.
[0016] Preferably, the specific process of the working electrode is: dispersing the plasma-etched Hofmann metal coordination polymer into a mixed solution consisting of ethanol, distilled water and a 5% by mass Nafion solution, and ultrasonically treating it to form a catalyst ink; and then coating it on a hydrophilic carbon cloth to obtain it.
[0017] The fifth aspect of the present invention proposes a nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst prepared by the above preparation method.
[0018] A sixth aspect of the present invention proposes the use of the above nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst in oxygen evolution reaction by electrolysis of water.
[0019] The beneficial effects of the present invention are:
[0020] The present invention proposes the use of plasma etching Hofmann coordination polymers to achieve rapid and deep reconstruction in oxygen evolution reaction, as well as preparation methods and applications. NiFe-Ni PBA nanosheet powder is first prepared by a simple precipitation method, and then the NiFe-Ni PBA nanosheet powder is treated with plasma etching to form carbon nitrogen vacancies and metal defects. CN vacancies and Ni ion vacancies can accelerate the reconstruction of NiFe-Ni PBA nanosheet powder, so that it is deeply reconstructed into NiOOH / FeOOH nanosheets. The deeply reconstructed P-NiFe-Ni PBA exhibits excellent activity and stability in alkaline electrolytes, alkaline simulated seawater, and alkaline actual seawater. It can efficiently and stably catalyze the electrolytic water oxygen evolution reaction under alkaline conditions, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The structural characterization diagrams of the Ni-Ni PBA prepared in Comparative Example 3 and the Fe-Ni-Ni PBA prepared in Comparative Example 4 are shown.
[0022] in, Figure 1 (a) and Figure 1 (d) is the XRD pattern of Ni-Ni PBA and Fe-Ni PBA. Figure 1 (b) and Figure 1 (e) is the SEM image of Ni-Ni PBA and Fe-Ni PBA. Figure 1 (c) and Figure 1 (f) is the EDS spectrum of Ni-Ni PBA and Fe-Ni PBA.
[0023] Figure 2 The performance characterization diagrams of the Re-Ni-Ni PBA prepared in Comparative Example 4 and the Re-Fe-Ni PBA prepared in Comparative Example 6 are shown in FIG. Figure 2 (a) is the LSV curve of Re-Ni-Ni PBA and Re-Fe-Ni PBA in 1M KOH. Figure 2 (b) is the Tafel plot of Re-Ni-Ni PBA and Re-Fe-Ni PBA.
[0024] Figure 3The XRD, SEM and EDS images of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are shown. Figure 3 (a) is the XRD pattern of NiFe-Ni PBA and P-NiFe-Ni PBA. Figure 3 (b) is a scanning electron microscope image of P-NiFe-Ni PBA at high magnification. Figure 3 (c) is the energy spectrum of P-NiFe-Ni PBA.
[0025] Figure 4 The transmission scanning, high resolution and electron diffraction patterns of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are shown. Figure 4 (a) and Figure 4 (d) is a scanning electron microscope image of NiFe-Ni PBA and P-NiFe-Ni PBA at high magnification. Figure 4 (b) and Figure 4 (e) is the high-resolution transmission image of NiFe-Ni PBA and P-NiFe-Ni PBA. Figure 4 (c) and Figure 4 (f) Selected area electron diffraction patterns of NiFe-Ni PBA and P-NiFe-Ni PBA, respectively.
[0026] Figure 5 EPR and Raman graphs of P-NiFe-Ni PBA prepared in Example 1 and NiFe-Ni PBA prepared in Comparative Example 1. Figure 5 (a) EPR graphs of P-NiFe-Ni PBA catalyst and NiFe-Ni PBA. Figure 5 (b) Raman graph of P-NiFe-Ni PBA catalyst and NiFe-Ni PBA.
[0027] Figure 6 XPS graphs of P-NiFe-Ni PBA prepared in Example 1 and NiFe-Ni PBA prepared in Comparative Example 1.
[0028] in Figure 6 (a) is the XPS graph of Ni 2p of NiFe-Ni PBA and P-NiFe-Ni PBA. Figure 6 (b) is the XPS graph of Fe 2p of NiFe-NiPBA and P-NiFe-Ni PBA. Figure 6 (c) is the XPS graph of C1s of NiFe-Ni PBA and P-NiFe-Ni PBA. Figure 6(d) is the XPS graph of N1s of NiFe-Ni PBA and P-NiFe-Ni PBA.
[0029] Figure 7 The synchronous radiation images of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are shown. Figure 7 (a) Ni K-edge XANES spectra of NiFe-Ni PBA and P-NiFe-Ni PBA; Figure 7 (b) and Figure 7 (c) EXAFS curves of Ni K-edge of NiFe-NiPBA and P-NiFe-Ni PBA. Figure 7 (d) Fe K-edge XANES spectra of NiFe-Ni PBA and P-NiFe-Ni PBA; Figure 7 (e) and Figure 7 (f) K-edge EXAFS curves of Fe of NiFe-Ni PBA and P-NiFe-Ni PBA.
[0030] Figure 8 These are performance test diagrams of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-Ni PBA prepared in Comparative Example 2. Figure 8 (a) is the LSV curve of Re-NiFe-Ni PBA and Re-P-NiFe-Ni PBA. Figure 8 (b) is the Tafel slope of Re-NiFe-Ni PBA and Re-P-NiFe-Ni PBA, Figure 8 (c) is the impedance curve of Re-NiFe-Ni PBA and Re-P-NiFe-NiPBA. Figure 8 (d) is the CV curve of Re-NiFe-Ni PBA at different scanning rates. Figure 8 (e) is the CV curve of Re-P-NiFe-Ni PBA at different scan rates. Figure 8 (f) Current density difference (Δj) between Re-NiFe-Ni PBA and Re-P-NiFe-Ni PBA as a function of scan rate.
[0031] Fig. 9 The structural characterization diagrams of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-Ni PBA catalyst prepared in Comparative Example 2. Fig. 9 (a) and Fig. 9 (d) is the XRD pattern of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst. Fig. 9 (b) and Fig. 9 (e) is the SEM image of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst under high magnification. Fig. 9 (c) and Fig. 9 (f) is the EDS graph of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst.
[0032] Fig.10 The structural characterization diagrams of the Re-P-NiFe-Ni PBA catalysts prepared in Example 2 and the Re-NiFe-Ni PBA catalysts prepared in Comparative Example 2 are shown. Fig.10 (a) and Fig.10 (d) is the transmission electron microscopy image of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst at low magnification. Fig.10 (b) and Fig.10 (e) is the high-resolution transmission image of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst. Fig.10 (c) and Fig.10 (f) is the selected electron diffraction pattern of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst.
[0033] Fig.11 Synchrotron radiation images of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-NiPBA catalyst prepared in Comparative Example 2. Fig.11 (a) is the K-edge XANES spectra of Ni in Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst. Fig.11 (b) and Fig.11 (c) K-edge EXAFS curves of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst. Fig.11 (d) is the K-edge XANES spectra of Fe in Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst. Fig.11 (e) and Fig.11 (f) K-edge EXAFS curves of Fe in Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst.
[0034] Fig.12 This is a catalytic characterization diagram of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2. Fig.12(a) is the stability diagram of Re-P-NiFe-Ni PBA catalyst at a voltage of 1.46 V vs RHE. Fig.12 (b) is the XRD pattern of Re-P-NiFe-Ni PBA catalyst after stability test. Fig.12 (c) is the SEM image of Re-P-NiFe-Ni PBA catalyst after stability test.
[0035] Fig.13 The catalytic characterization diagrams of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-NiPBA catalyst prepared in Comparative Example 2 in alkaline simulated seawater and alkaline actual seawater of different concentrations. Fig.13 (a) Fig.13 (b) and Fig.13 (c) is the LSV curve of Re-P-NiFe-Ni PBA catalyst and Re-NiFe-Ni PBA catalyst in 0.5M NaCl, 1M NaCl and real seawater. Fig.13 (d) Fig.13 (e) and Fig.13 (f) is the Tafel slope diagram fitted for Re-P-NiFe-Ni PBA catalyst and Re-NiFe-Ni PBA catalyst in 0.5M NaCl, 1M NaCl and actual seawater. Fig.13 (g) The stability test of Re-P-NiFe-Ni PBA in actual seawater at a voltage of 2.07 V vs RHE. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0038] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0039] Embodiment 1:
[0040] A method for preparing a plasma-etched nickel-iron Hofmann metal coordination polymer (P-NiFe-Ni PBA), comprising the following steps:
[0041] S1, 0.4mmol K 2 Ni(CN) 4 Dissolve in 20 mL DIW to prepare solution A, and then take 0.3 mmol Ni(NO 3 ) 2 6H 2 O and 0.1mmol FeSO 4 9H 2 O prepared solution B in 20 ml DIW, after fully stirring, the A and B solutions were mixed and stirred for 3 minutes, and the obtained solution was aged at room temperature for 24 hours. After the reaction, the product was centrifuged at 9000 rpm and washed alternately with ethanol and deionized water for more than 3 times, and then dried at 70 ° C to finally obtain NiFe-Ni PBA nanosheet powder;
[0042] S2. The NiFe-Ni PBA nanosheet powder was evenly spread on a quartz plate, placed in a radio frequency plasma reaction device, and plasma etching was performed for 10 minutes under the conditions of an argon atmosphere, a cavity pressure of 50 Pa, and a plasma power of 300 W to obtain a P-NiFe-Ni PBA nanosheet sample.
[0043] Embodiment 2:
[0044] A method for preparing a nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst (Re-P-NiFe-Ni PBA),
[0045] The method is obtained by subjecting the plasma-etched nickel-iron Hofmann metal coordination polymer (P-NiFe-NiPBA) of Example 1 to oxygen evolution reaction activation, which specifically comprises the following steps:
[0046] P-NiFe-Ni PBA nanosheet powder was loaded on hydrophilic carbon cloth as a working electrode, Hg / HgO as a reference electrode, and a carbon rod as a counter electrode to form a three-electrode system. 1M KOH solution was used as the electrolyte and activated by constant voltage at a voltage of 1.82 V and an activation time of 11 h to obtain a nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst, which was recorded as Re-P-NiFe-Ni PBA.
[0047] The preparation method of the working electrode includes the following steps: dispersing 5 mg of nanosheet powder into a mixed solution consisting of 270 μL of ethanol, 200 μL of distilled water and 30 μL of a 5% Nafion solution, and ultrasonicating for 30 minutes to form a slurry ink. 2 The hydrophilic carbon cloth is coated on the surface of the hydrophilic carbon cloth. The hydrophilic carbon cloth is soaked in concentrated sulfuric acid for 24 hours, then cleaned with deionized water and alcohol ultrasonically, and dried at 60°C for storage.
[0048] Comparative Example 1:
[0049] Preparation of nickel-iron Hofmann metal coordination polymer (NiFe-Ni PBA):
[0050] The difference between this comparative example and Example 1 is that step S2 is missing, and the rest is the same as Example 1.
[0051] Comparative Example 2:
[0052] Preparation of nickel-iron Hofmann metal coordination polymer catalyst (Re-NiFe-NiPBA) activated by oxygen evolution reaction:
[0053] The difference of this comparative example is that the P-NiFe-Ni PBA in Example 2 is replaced by "NiFe-Ni PBA prepared in Comparative Example 1", and the rest is the same as Example 2.
[0054] Comparative Example 3:
[0055] Preparation of nickel cyanide (Ni-Ni PBA):
[0056] It was prepared by a simple precipitation method. 0.096 g K 2 Ni(CN) 4 Potassium was dissolved in 20 ml of deionized water to prepare solution A, and 0.04 mmol of Ni(NO 3 ) 2 6H 2 O was dissolved in 20 ml of deionized water to prepare solution B. After the A and B solutions were stirred evenly, solution A was slowly poured into solution B and stirred for 3 min. The resulting solution was aged at room temperature for 24 h. After the reaction was completed, the mixture was centrifuged at 9000 rpm and washed alternately with ethanol and deionized water, and then dried at 70 ° C to obtain Ni-Ni PBA nanosheet powder.
[0057] Comparative Example 4:
[0058] Preparation of nickel-containing Hofmann metal coordination polymer catalyst (Re-Ni-Ni PBA) after activation by oxygen evolution reaction:
[0059] The difference of this comparative example is that the P-NiFe-Ni PBA in Example 2 is replaced by "Ni-Ni PBA prepared in Comparative Example 3", and the rest is the same as Example 2.
[0060] Comparative Example 5:
[0061] Nickel ferric cyanide (Fe-Ni PBA):
[0062] It was prepared by a simple precipitation method. 0.096 g K 2 Ni(CN) 4 Potassium was dissolved in 20 ml of deionized water to prepare solution A, and 0.04 mmol of Fe 2 (SO 4 ) 3 9H 2 O was dissolved in 20 ml of deionized water to prepare solution B. After the A and B solutions were stirred evenly, solution A was slowly poured into solution B and stirred for 3 min. The resulting solution was aged at room temperature for 24 h. After the reaction was completed, the mixture was centrifuged at 9000 rpm and washed alternately with ethanol and deionized water, and then dried at 70 ° C to obtain Fe-Ni PBA nanosheet powder.
[0063] Comparative Example 6:
[0064] Preparation of nickel-iron Hofmann metal coordination polymer catalyst (Re-Fe-NiPBA) activated by oxygen evolution reaction:
[0065] The difference of this comparative example is that the P-NiFe-Ni PBA in Example 2 is replaced by "Fe-Ni PBA prepared in Comparative Example 5", and the rest is the same as Example 2.
[0066] Test example:
[0067] The nanosheet powders obtained in Examples 1 to 2 and Comparative Examples 3, 4, and 6 were characterized and tested for performance:
[0068] The structural characterization diagrams of the Ni-Ni PBA prepared in Comparative Example 3 and the Fe-Ni PBA prepared in Comparative Example 4 are shown in FIG. Figure 1 shown. Figure 1 (a) and Figure 1 (d) is the XRD pattern of Ni-Ni PBA and Fe-Ni PBA, which have typical PBA crystal structures. Figure 1 (b) and Figure 1 (e) is a SEM image of Ni-Ni PBA and Fe-Ni PBA, both of which show a sheet-like structure, but Ni-Ni PBA is a smaller nanosheet. Compared with the Ni-Ni PBA of Comparative Example 3, the Fe-Ni PBA nanosheet of Comparative Example 4 is thicker. Figure 1 (c) and Figure 1 (f) is the EDS spectrum of Ni-Ni PBA and Fe-Ni PBA. The atomic content of Ni in Ni-Ni PBA is 16.8%, and the atomic content of Ni and Fe in Fe-Ni PBA is 12.5% and 10.4%, respectively.
[0069] The performance characterization diagrams of the Re-Ni-Ni PBA prepared in Comparative Example 4 and the Re-Fe-Ni PBA prepared in Comparative Example 6 are shown in FIG. Figure 2 shown. Figure 2 (a) is the LSV curve of Ni-Ni PBA and Fe-Ni PBA. The OER activity of Ni-Ni PBA and Fe-Ni PBA in 1M KOH was studied. Ni-Ni PBA and Fe-Ni PBA have poor OER activity. In addition, Figure 2 (b) Tafel slopes of Ni-Ni PBA and Fe-Ni PBA, which also have poor reaction kinetics.
[0070] The XRD, SEM and EDS images of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are as follows: Figure 3 shown. Figure 3 (a) is the XRD pattern of P-NiFe-Ni PBA and NiFe-Ni PBA, both of which have typical PBA crystal structure, and plasma etching does not change their crystal phase. Figure 3 (b) is the SEM image of P-NiFe-Ni PBA, showing a uniform nanosheet morphology. Figure 3 (c) is the EDS image of P-NiFe-Ni PBA. After plasma etching, the Ni / Fe ratio is 5.7.
[0071] The transmission scanning, high resolution and electron diffraction patterns of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are as follows: Figure 4 shown. Figure 4 (a) and Figure 4 (d) is the transmission scan of NiFe-Ni PBA and P-NiFe-Ni PBA, both of which are uniform nanosheets with a size of 60-70nm. Plasma etching does not change the morphology of the nanosheets. Figure 4 (b) and Figure 4 (e) is a high-resolution image of NiFe-Ni PBA and P-NiFe-Ni PBA, where lattice fringes of 0.19 and 0.23 can be clearly seen, belonging to the (234) and (240) crystal planes of PBA, respectively. Figure 4 (c) and Figure 4(f) is the selected area electron diffraction pattern of NiFe-Ni PBA and P-NiFe-Ni PBA, proving that plasma does not change the PBA crystal phase.
[0072] The electron paramagnetic resonance and Raman patterns of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are shown in FIG. Figure 5 shown. Figure 5 (a) is the electron paramagnetic resonance image of P-NiFe-Ni PBA and NiFe-Ni PBA. A significantly enhanced symmetry signal was observed at a g factor of 2.03, indicating the presence of a large number of CN vacancies. Figure 5 (b) Raman spectra of P-NiFe-Ni PBA and NiFe-Ni PBA, at 200-600 cm -1 The vibration of metal-carbon bonds and metal-nitrogen bonds is shown in the range, and the obvious weakening and disappearance of Ni-NC bonds and Fe-CN bonds further proves the generation of a large number of CN vacancies.
[0073] The XPS graphs of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are as follows: Figure 6 As shown. NiFe-Ni PBA and P-NiFe-Ni PBA both contain Ni, Fe, C and N. Figure 6 The characteristic peaks at 855.4 and 872.9 eV in (a) belong to Ni 2+ Ni 2p 3 / 2 and Ni 2p 1 / 2 , the characteristic peaks at 856.1 and 873.4 eV belong to Ni 3+ Ni 2p 3 / 2 and Ni 2p 1 / 2 ,After plasma etching, the XPS peak of Ni is significantly reduced, indicating that the Ni content is reduced. Figure 6 (b) corresponds to Fe 2+ and Fe 3+ , Figure 6 (c) and Figure 6 In the XPS images of C1s and N1s in (d), the existence of C≡N can be seen, further proving the successful synthesis of PBA.
[0074] The synchrotron radiation patterns of the P-NiFe-Ni PBA prepared in Example 1 and the NiFe-Ni PBA prepared in Comparative Example 1 are as follows: Figure 7 shown. Figure 7 (a) and Figure 7(d) is the X-ray absorption near-edge spectra of Ni K-edge and Fe K-edge of NiFe-Ni PBA catalyst and P-NiFe-Ni PBA. The valence states of Ni and Fe elements have not changed. Figure 7 (b, c) and Figure 7 (e, f) are the extended X-ray absorption fine structure (EXAFS) images of Ni K-edge and Fe K-edge. The strength of Ni-C bond and Ni-N bond decreases after plasma etching, and the bond length of Fe-C and Fe-N bonds changes, and the peak intensity decreases and the disorder increases, indicating that CN vacancies are generated in P-NiFe-Ni PBA and that Ni atoms become coordinatively unsaturated metal sites after plasma bombardment.
[0075] The performance characterization diagrams of the Re-P-NiFe-Ni PBA prepared in Example 2 and the Re-NiFe-Ni PBA prepared in Comparative Example 2 are shown in FIG. Figure 8 In the three-electrode system, NiFe-Ni PBA and P-NiFe-Ni PBA were used as working electrodes, carbon rods were used as counter electrodes, Hg / HgO was used as reference electrodes, and 1 M KOH was used as electrolyte to characterize the catalytic activity. Figure 8 (a) It can be seen that Re-P-NiFe-Ni PBA at 10 mA cm -2 The overpotential is only 220mV at a current density of , which is much higher than Re-NiFe-NiPBA. In the process of oxygen evolution in water electrolysis, the theoretical value of the oxygen evolution overpotential is usually related to many factors, such as electrode materials, electrolyte properties and temperature. Generally speaking, the standard potential of the oxygen evolution reaction is about 1.23V, but due to the existence of overpotential, the actual oxygen evolution potential is often higher than this value. Therefore, the introduction of a catalyst can greatly reduce the overpotential of water electrolysis, and the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 has higher activity. Figure 8 (b) shows that compared with Re-NiFe-NiPBA (60.94mV dec -1 ), Re-P-NiFe-Ni PBA has a smaller Tafel slope (29.82mV dec -1 ). Figure 8 (c) is the Nyquist plot of Re-P-NiFe-Ni PBA and Re-NiFe-Ni PBA. After Ar plasma etching, the impedance is significantly reduced, indicating that the charge transfer rate is increased. Figure 8 (d) Figure 8 (e) and Figure 8(f) The electrochemical active area diagram and current density difference and scan rate function diagram of Re-NiFe-Ni PBA and Re-P-NiFe-NiPBA, respectively, indicating that after plasma etching, the electrochemical area increases and more OER active sites are exposed.
[0076] The XRD, SEM and EDS images of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-Ni PBA catalyst prepared in Comparative Example 2 are as follows: Fig. 9 shown. Fig. 9 (a) and Fig. 9 (d) is the XRD pattern of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-NiPBA catalyst. It can be seen that the phases of the reconstructed catalysts can match well with NiOOH and FeOOH, indicating that they can be completely converted into active substances, metal hydroxide oxides, after reconstruction. Fig. 9 (b) and Fig. 9 It is observed in the SEM image of (e) that after reconstruction, the Re-NiFe-Ni PBA catalyst and the Re-P-NiFe-Ni PBA catalyst are transformed into thinner nanosheet morphology. Due to their small nanosize, fusion and regrowth may occur during the reconstruction process. Fig. 9 (c) and Fig. 9 (f) is the EDS image of Re-NiFe-Ni PBA catalyst and Re-P-NiFe-Ni PBA catalyst. The Ni / Fe ratios of the reconstructed Re-NiFe-NiPBA catalyst and Re-P-NiFe-Ni PBA catalyst are 7.7 and 7.03, respectively. Compared with the ratio before reconstruction, the Ni / Fe ratio is reduced, indicating that Fe dissolution occurs during the reconstruction process.
[0077] The TEM, high resolution and electron diffraction ring patterns of the P-NiFe-Ni PBA prepared in Example 2 and the NiFe-Ni PBA prepared in Comparative Example 2 are as follows: Fig.10 shown. Fig.10 (a) and Fig.10 (d) is the TEM image of Re-NiFe-Ni PBA catalyst and Re-NiFe-Ni PBA catalyst. It can be clearly observed that the reconstructed catalyst is assembled from ultrathin nanosheets. Fig.10 (b) and Fig.10 (e) is a high-resolution image of the reconstructed catalyst, where the lattice fringes corresponding to NiOOH and FeOOH can be clearly observed, proving that both prepared catalysts can be completely reconstructed into NiOOH and FeOOH. Fig.10 (c) and Fig.10The electron diffraction ring pattern (f) can further prove that it can be completely reconstructed. In addition, it can be observed that the reconstructed phase of NiFe-NiPBA after plasma etching is more amorphous, which may be one of the main reasons for its excellent activity.
[0078] The synchrotron radiation patterns of the Re-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-Ni PBA catalyst prepared in Comparative Example 2 are as follows: Fig.11 shown. Fig.11 (a) and Fig.11 (b) is the XANES spectrum of Ni K-edge and Fe K-edge. It can be seen that the energy of Re-P-NiFe-Ni PBA catalyst and Re-NiFe-Ni PBA catalyst is higher than that of NiOOH, indicating that the Ni oxidation state in Re-P-NiFe-Ni PBA catalyst and Re-NiFe-Ni PBA catalyst is higher than 3 + However, the Ni K-edge energy of the Re-P-NiFe-NiPBA catalyst is higher than that of the Re-NiFe-Ni PBA catalyst, indicating that the plasma-activated Ni is more easily oxidized to a high valence state and has higher OER activity. The valence state of Fe in the Re-P-NiFe-Ni PBA catalyst and the Re-NiFe-Ni PBA catalyst is higher than that of FeOOH by 3 + , but plasma etching has little effect on the valence state of Fe. Fig.11 (b, c) and Fig.11 (e, f) are the EXAFS graphs of Ni K-edge and Fe K-edge. The Re-NiFe-Ni PBA catalyst and the Re-P-NiFe-NiPBA catalyst have Left and right The peaks on the left and right can be assigned to Ni-O bonds and Ni-Ni bonds, respectively. The Ni-O bond position of the Re-P-NiFe-Ni PBA catalyst is the same as that of the Re-NiFe-Ni PBA, but the Ni-Ni bond shifts to the left, indicating that the bond length of the Ni-Ni bond decreases, and the decrease in intensity indicates an increase in disorder. It can be observed in the EXAFS spectrum of the Fe K-edge that compared with Re-NiFe-Ni PBA, the Fe-O and Fe-Fe bond lengths of the Re-P-NiFe-Ni PBA shift to the left and right, respectively, and the intensity decreases, indicating that the Fe-O bond becomes shorter, the Fe-Fe bond becomes longer, and the disorder increases. This indicates that the disorder increases after reconstruction, and more vacancies may be generated.
[0079] The stability characterization diagram of the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 is as follows Fig.12The current density of Re-P-NiFe-Ni PBA at an overpotential of 1.46 V vs. RHE can be stabilized at 10 mA cm for 800 h. -2 .and Fig.12 (b) and Fig.12 (c) The XRD and SEM images after stabilization show that the phases are composed of NiOOH and FeOOH, and the morphology is still assembled by ultrathin nanosheets.
[0080] In order to make the Re-P-NiFe-Ni PBA catalyst prepared in Example 2 and the Re-NiFe-NiPBA catalyst prepared in Comparative Example 2 more widely used, oxygen evolution reaction tests were carried out in alkaline simulated seawater and alkaline actual seawater of different concentrations. The test results are shown in FIG. Fig.13 As shown. Fig.13 As can be seen from (af), the NiFe-Ni PBA after plasma etching is improved in all three seawater electrolytes. -2 It can stably catalyze OER for up to 150 hours at an industrial-level current density, showing good stability.
[0081] Embodiment 3:
[0082] The difference between this embodiment and embodiment 1 is that:
[0083] In step S1, K 2 Ni(CN) 4 ,Ni(NO 3 ) 2 6H 2 O, FeSO 4 9H 2 O were 0.3mmol, 0.2mmol, and 0.05mmol, respectively;
[0084] In step S2, the pressure, plasma power, and etching treatment time are 60 Pa, 250 W, and 15 min, respectively;
[0085] The rest is the same as in Example 1.
[0086] Embodiment 4:
[0087] The difference between this embodiment and embodiment 1 is that:
[0088] In step S1, K 2 Ni(CN) 4 ,Ni(NO 3 ) 2 6H 2 O, FeSO 4 9H2 O were 0.5mmol, 0.4mmol, and 0.15mmol, respectively;
[0089] In step S2, the pressure, plasma power, and etching treatment time are 40 Pa, 350 W, and 8 min, respectively;
[0090] The rest is the same as in Example 1.
[0091] The structures and properties of the polymers obtained in Examples 3 and 4 are similar to those in Example 1.
[0092] Embodiment 5:
[0093] The difference between this embodiment and embodiment 2 is that the voltage is 1V, the activation time is 15h, and the rest is the same as embodiment 2.
[0094] Embodiment 6:
[0095] The difference between this embodiment and embodiment 2 is that the voltage is 3V, the activation time is 8h, and the rest is the same as embodiment 2.
[0096] The performance of the catalysts prepared in Examples 5 and 6 is similar to that in Example 2.
[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a plasma-etched Hofmann metal coordination polymer, characterized in that: The following steps are involved: S1, dissolving potassium tetracyanonickelate in deionized water to prepare solution A, and then dissolving ferrous sulfate and nickel nitrate in deionized water to prepare solution B, then mixing solution A and solution B, standing at room temperature for a period of time, centrifuging, washing, and drying to obtain NiFe-Ni PBA nanosheet powder; S2. Evenly spread NiFe-Ni PBA nanosheet powder on a quartz plate, place it in a radio frequency plasma reaction device, and perform plasma etching treatment under an argon atmosphere to obtain the nanosheet.
2. The preparation method according to claim 1, characterized in that: In S1, the molar ratio of potassium tetracyanonickelate, nickel nitrate and ferrous sulfate is (3-5):(2-4):(0.5-1.5).
3. The preparation method according to claim 1, characterized in that: In S2, the pressure of the plasma etching treatment is 40-60 Pa, the power is 250-350 W, and the time is 8-15 min.
4. The plasma-etched Hofmann metal coordination polymer obtained by the preparation method according to any one of claims 1 to 3.
5. Use of the plasma-etched Hofmann metal coordination polymer according to claim 4 in the preparation of nickel oxyhydroxide / iron oxyhydroxide heterostructure catalysts.
6. A method for preparing a nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst, characterized in that: The plasma-etched Hofmann metal coordination polymer described in claim 4 is loaded on a hydrophilic carbon cloth as a working electrode, Hg / HgO as a reference electrode, and a carbon rod as a counter electrode to form a three-electrode system, and potassium hydroxide is used as an electrolyte to activate it by a constant voltage method to obtain the obtained product.
7. The preparation method according to claim 6, characterized in that: In the constant voltage method for activation, the voltage is 1 to 3 V and the activation time is 8 to 15 hours.
8. The preparation method according to claim 6, characterized in that: The specific process of the working electrode is as follows: the plasma-etched Hofmann metal coordination polymer is dispersed in a mixed solution consisting of ethanol, distilled water and a 5% by mass Nafion solution, and ultrasonically treated to form a catalyst ink; Then it is coated on a hydrophilic carbon cloth.
9. The nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst prepared by the preparation method according to any one of claims 6 to 8.
10. Use of the nickel oxyhydroxide / iron oxyhydroxide heterostructure catalyst according to claim 9 in oxygen evolution reaction by electrolysis of water.
Citation Information
Patent Citations
Preparation method of Huffman type coordination polymer nano material
CN112048072A
Cited By
NiOOH-coated NiFe-PBA modified carbon cloth self-supporting electrode and preparation method and detection application thereof
CN120971534A